Corporate governance in the telecommunications industry - Jeon, Yeongtae (KDI School, 1998)
Technological, regulatory, and economic forces have been changing the telecommunications industry. Korea Telecom, the leading telecommunications company in Korea, is experiencing privatization, deregulation, and market opening which is resulting in the weakening of its monopolistic position. This paper aims to analyze the governance structure of telecommunications companies by reviewing the existing literature and conducting case studies of telcos in different stages of privatization. This study analyzes several telecommunications companies, such as AT&T and BT – the leading telcos with diffuse ownership – and Deutsche Telekom and France Telecom – those still regulated by their respective government. The key findings obtained through the case studies are as follows: First, this study did not find a significant relationship between firm performance and the composition of the board. Second, in the face of rapidly deregulating environment, the telcos have begun to give emphasis on the form of executive compensation by increasing the variable portion of the compensation. Finally, the market for corporate control is becoming an important mechanism for resolving owner-manager conflicts after privatization and deregulation.
Thesis(Master) --KDI School:Master of Strategy & International Management,1998